A Broad Examination of Mental Health Literacy Among College Students in the United States - Susan M. Hannan; Tony T. Wells (SLACK Incorporated, 2023)
Background: High levels of mental health literacy (MHL) have been linked to the ability to correctly recognize certain problems as mental health issues, which then may lead to effective help-seeking behaviors. Most research on MHL has focused on a limited number of psychiatric diagnoses, using Australian samples. Objective: This study aimed to investigate various components of MHL in a large sample of undergraduate students in the United States. Methods: We conducted a vignette-based study with 843 undergraduate students. Six psychiatric diagnoses (and two "non-disordered" scenarios) were represented in distinct vignettes. Participants rated the severity of each vignette character's problem, the helpfulness of numerous treatment options, and the likelihood that different etiological factors contributed to the character's problem. Key Results: Across all clinical vignettes, therapy/counseling was perceived to be the most helpful treatment. Participants rated "personal weakness/lack of willpower" as contributing the most to the alcohol use disorder (AUD) character's problems. Our hypothesis related to how perceptions of etiology may impact participants' perceptions of different types of treatment was partially supported for the depression character. When participants described the depression character as having a "psychological/mental health problem," they were more likely to perceive therapy/counseling as being helpful compared to medication. Conclusions: Participants recognized most of the psychiatric diagnoses as a mental health problem, acknowledged the seriousness of the presenting problems, and recommended effective help-seeking behavior. However, undergraduate U.S. students could benefit from increased MHL specifically related to AUD. [HLRP: Health Literacy Research and Practice. 2023;7(4):e207-e214.]